Physiological quality of sorghum (Sorghum bicolor L. Moench) seed subjected to defoliation and drought stress. - Montes, Noé; González, V. A.; Mendoza, Leopoldo (Agronomía Mesoamericana, 2016)
The effects of defoliation were studied in sorghum plants subjected to drought stress in pre and post-blooming stages. The quality was appraised on the seed obtained from a sorghum line evaluated under greenhouse conditions in 1991, at the Colegio de Postgraduados, Montecillo, Mexico. The pre-blooming drought stress consisted of withholding the water to the plants at their primary branch differentiation stage, whereas during the post-blooming drought stress, the water was withheld at theearly blooming stage. The defoliation levels (0, 40 and 80% of the total leaf area) were conducted during each drought stress treatment. In general, the germination was reduced as the seed size decreased. The germination percentage was above 80% for the 3 and 3.5 mm seed sizes; while for the 2.5 mm seed size, the germination decreased rapidly in plants that were not defoliated in both moisture conditions. This indicates that adverse factors such as drought stress and defoliation can reduce seed size, but it the same time it can also stimulate the seed germination.